A dramatic increase in serum CK levels after switching from oral to intravenous administration of LEV. Issue 1 (11th October 2019) - Takemoto, Mami; Yunoki, Taijun; Sato, Kota; Hishikawa, Nozomi; Yamashita, Toru; Ohta, Yasuyuki; Shang, Jingwei; Abe, Koji
Abstract: The authors report on a 22‐year‐old Japanese woman who started oral administration of 1000 mg levetiracetam (LEV) for her epilepsy after the second convulsive seizure. She was free from seizures for the subsequent 111 days, but a third tonic‐clonic seizure happened and she was transferred to our hospital (Day 1). Her consciousness state was drowsy and 1000 mg LEV continued for two days, but intravenously. Although her state became clear, her serum creatine kinase (CK), myoglobin (Mb), and creatine (Cre) levels were significantly elevated (18 179 IU/L, 2783 ng/mL, and 0.8 mg/mL) with a peak at Day 5 of CK 26, 189 IU/L. After stopping intravenous injection of LEV, serum CK returned to its normal level promptly. The present case suggests that we should take more care in monitoring for rhabdomyolysis on switching from oral to intravenous administration of LEV.